Igbo Apprenticeship System and its Implication on Economic Development in South East Nigeria - Emmanuel Chinedu Okoye; Hendra Prasetyo (PT. Altaf Publishing Corp, 2026)
There are significant structural issues of youth unemployment and the high mortality rate of new enterprises (micro-businesses) in South East Nigeria. Millions of youngsters are leaving school without the skills necessary to lead successful businesses. In traditional formal education, many schools are not focused on developing entrepreneurial skills for students, leaving many young people without a viable livelihood. This qualitative study aims to examine the Igba-Boi (Indigenously known apprenticeship system) and its implications for enterprise survival and regional economic development. Semi-structured in-depth interviews with new young entrepreneurs and the business masters, who have been in business for a long time, were used in the field to collect data, and were analyzed according to a rigid thematic framework, in the main business clusters of the region. The results showed that ongoing post-settlement mentorship from the former masters has a direct impact on business survival, creating a buffer against credit defaults, capital misallocation, and supply chain. Moreover, it confirmed that the traditional certification, carried out in the public discharge ceremony, represents a huge social signal that assures lateral mobility in the profession and managerial safety in regional trade networks. But there was a major structural problem: this informal qualification is not recognized by formal financial institutions, and partner organisations often have a way of discarding such a qualification because of the lack of standardized government recognition. The study found that the Igba-Boi system has not only continued to be an irreplaceable enabler of private sector development in Nigeria but is also an extremely resilient mechanism for youth job creation. To make the maximum contribution to the economy, it is necessary to implement targeted policy measures to formalize and safeguard these indigenous qualifications, thus creating a link between informal markets and formal financial markets and fostering sustainable national development.